Customer acceptance on affordable housing by PR1MA / Mohd Shazlan Shah Kassim and Muhammad Hanif Borhannuddin - Kassim, Mohd Shazlan Shah; Borhannuddin, Muhammad Hanif (Faculty of Business and Management, 2015)
This research presents the customer’s acceptance towards affordable housing by PR1MA. In the introduction chapter, there are problem statement, research questions, research objectives, the significant of study as well as the scope of study at PR1MA. This research also presents a review of literature that focuses price, quality and location. The hypotheses are used to investigate the relationship between customer acceptance and the three independent variables (price, quality, location). There is also research methodology, whereby the research design, exploratory, descriptive and causal research were used. The population size and sample size do affect the number of sample respondents. To collect data, we used SPSS program for descriptive statistics testing as well as hypotheses testing. This research is to show the effects of price, quality and location on customer acceptance towards affordable housing by PR1MA. All the results obtained from SPSS were used to answer the objectives presented in this research. As for recommendations, there are several that have been suggested based on the results of this research.